Benefits of Black Seed According to Hadith - Fauzan Fadhillah; Naan Naan (Gunung Djati Conference Series, 2021)
This study aims to discuss the meaning of Black Seed according to the hadith. This research is a qualitative type by applying literature study to interpret the hadith about Black Seed 'with a content analysis approach. The results and discussion of this study include the meaning of Black Seed ", hadith and an explanation of Black Seed", and the meaning of Black Seed ". This study concluded that the meaning of Black Seed "medicine for all kinds of diseases depends on what kind of disease, then consuming Black Seed" can also vary as well as the dosage that must be given to the patient. Then the composition of Black Seed 'has many benefits, especially to increase endurance.